PENERAPAN TANGGUNG JAWAB PELAKU USAHA DALAM MENJUAL GAS ELPIJI 3 KG KEPADA KONSUMEN YANG TIDAK MAMPU - Syahrial Halomoan; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The responsibility of the businessperson for the sale of 3 kg LPG to consumers who cannotafford it in Pekanbaru City, Riau Province needs to be carried out, because there are still manybusinesses or bases that still sell 3 kg LPG to consumers who are more capable and for industry. Asa result of the treatment of business actors or bases, the poor people cannot get 3 kg of LPG gaswhich is their right to household needs such as cooking. Of course many consumer rights as a 3 kgLPG gas user feel that their rights are violated, business people should be responsible in treatingconsumers fairly and not discriminating and must follow the prevailing laws and regulationsThe problems discussed are first, regarding the basis of the base is not responsible for thesales of 3 kg LPG to consumers who are not capable and Second What is the base effort to beresponsible for the sale of 3 kg LPG to consumers who can not afford. The research method used isempirical research, another term used is Sociological legal research also called field research andthis research is descriptive. In data collection, the type of data used in this study is primary dataand secondary data, namely directly through respondents (field), Law No. 8 of 1999 concerningConsumer Protection, Law No. 20 of 2008 concerning Micro, Small, and Intermediate (UMKM),Civil Code, Presidential Regulation No. 104/2007 concerning Provision, Distribution andDetermination of Three Kilogram Liquefied Petroleum Gas Tubes, Regulation of the Minister ofMineral Resources No. 26 of 2009 concerning Liquefied Supply and Distribution Petroleum Gas,legal journals and books related to research. This data analysis is carried out qualitatively anddeductively deduced.From the results of research conducted by the author, it was found that there were stillbusiness players or bases who were not responsible for the sale of 3 kg LPG to consumers whocould not afford, so that the poor consumers were indirectly harmed. So, based on this, it isrequired the responsibility of the business actor in the sale of 3 kg LPG to consumers who cannotafford it.